IN SILICO DOCKING OF QUERCETIN COMPOUND AGAINST THE HELA CELL LINE PROTEINS - Muthukala, Borappa; Sivakumari, Kanakarajan; Ashok, Kamalanathan (International Journal of Current Pharmaceutical Research, 2015)
The present molecular docking study can be useful for the design and development of novel compound having better inhibitory activity against human cervical cancer cell line proteins. The docking scores were highest for cellular tumor antigen p53 with -4.52 kcal/mol with the stronger interaction followed by Caspase-3 (-4.09 kcal/mol.), Mucosal address in cell adhesion molecule 1(-4.0 kcal/mol) and the last score was found in the NF-kappaB (-2.83 kcal/mol) and the LogP, lower hydrogen bond counts, confirming the capability of the Quercetin for binding at the active site of the receptor. These potential drug candidates can further be validated in wet lab studies for its proper function.